The role of the new development strategy of Uzbekistan in educating a spiritually mature person - Zakirjanov Nematjon Ziyoviddin ugli; Kambarov Abdujabbar Bokhrolievich (Zien Journals, 2024)
This article examines the decisive role of the new development strategy of Uzbekistan in the development of spiritually mature individuals. As the nation embarks on a transformational journey, the convergence of economic, social, and cultural aspects is evident in the formation of enlightened citizens. The article examines the theoretical foundations of spiritual maturity through a comprehensive literature review and examines the methods used to weave this concept into the fabric of development in Uzbekistan. The main part of the article analyzes the results achieved so far, highlights the complex connections between national development and the upbringing of a spiritually mature person. The conclusion provides insight into the broader implications of this strategy and offers suggestions for further improvement
Keywords: Uzbekistan; development strategy; spiritual maturity